The stationary local sojourn time in single server tandem queues with renewal input. (1999) - Gall, Pierre Le
Abstract : We start from an earlier paper evaluating the overall sojourn time to derive the local sojourn time in stationary regime, in a single server tandem queue of ( m + 1 ) stages with renewal input. The successive service times of a customer may or may not be mutually dependent, and are governed by a general distribution which may be different at each sage.